Pengaruh Keterampilan Teknis Terhadap Produktivitas Karyawan PT Sumber Bara Abadi Melalui Lingkungan Kerja Sebagai Variabel Mediator - Reny Ramahdani; Vera Anitra; Achmad Efendi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Employee productivity is a crucial element in determining the operational success of a company, which is influenced by internal factors such as technical skills and working conditions. The purpose of this study is to analyze the extent to which technical skills contribute to increasing employee productivity at PT Sumber Bara Abadi, considering the role of the work environment as a mediating variable. The research approach is quantitative, using the Structural Equation Modeling (SEM) method with the Partial Least Squares (PLS) technique. The population in this study includes all 70 permanent employees of the company, where the entire population was used as the sample through saturated sampling due to its limited size. Data collection was conducted using a questionnaire designed to assess aspects of technical skills, work environment, and employee productivity levels. The analysis results indicate that technical skills have a positive and significant influence on productivity, and technical skills also have a positive and significant influence on the work environment. Additionally, the work environment is also proven to have a positive and significant influence on employee productivity. Other findings confirm that technical skills influence employee productivity through the work environment. Based on these results, it is recommended that companies develop technical skills training programs integrated with strategies for creating a conducive work environment to promote optimal and sustainable productivity.